The Optimization of Tuna Fish and Banana Blossoms into Abon Modified Products in Puger District, Jember Regency - Ninna Rohmawati; Anita Dewi Moelyaningrum; Eri Witcahyo (Warta Pengabdian, 2019)
Puger is the largest fish producing sub-district in Jember district, which also has a prevalence of high nutritional problems. During this time there are “mitra” who are a group of fish processors and marketers (POKLAHSAR) namely "Ekonomi Puger Bahari (EPB)" and "Duta Tongkol" who try to explore the potential of fish in Puger District. Tuna fish abon produced by “mitra” has a soft texture (srundeng like) so that it is less preferred by consumers therefore this paper argues that there's a need to add banana blossoms as a compound, does not have P-IRT (product permit), and the marketing of the product is not optimal. The author believes that if there is a need for development in terms of products implemented in several respects, among others: 1) Training on modified abon production; 2) Management of P-IRT; 3) Training in business financing and marketing management; 4) Production and marketing assistance. This activity can help partner problems. Expected targets and outcomes, namely: 1) Abon modified tuna and banana heart products that have P-IRT, high protein content is expected to be a solution to KEP nutritional problems; 2) The method of business financing management and appropriate marketing management has been achieved. In addition to directly, partners have marketed their products through social networks and resellers. Partners experience additional turnover and number of buyers; 3) Mastery of skills in the form of skills makes modification abon. This activity has an impact on up-dating science and technology in partners. Keywords: abon modified; tuna fish; banana blossom; optimization.